1997
DOI: 10.1002/(sici)1097-4628(19971205)66:10<1869::aid-app4>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate-functionalized latexes: Film formation and tensile properties

Abstract: Latexes functionalized with isocyanate groups were prepared by carrying out the emulsion terpolymerization of dimethyl meta-isopropenyl benzyl isocyanate (TMI) with methyl methacrylate and n-butyl acrylate. The film formation of these latexes and the tensile properties of the resulting latex films were studied. The effect of TMI concentration on the film properties was investigated. The locus of the isocyanate groups in the latex particles was controlled by using different polymerization processes. The locus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…They concluded that the NCO groups were evenly distributed throughout the particles under starved, semi‐batch conditions. The tensile properties of films prepared from those latexes gave a clear indication that TMI was contributing to crosslinking . Although they used a different surfactant (sodium dihexyl sulfosuccinate, MA‐80), a lower BA/MMA ratio (≈60/40; wt./wt.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the NCO groups were evenly distributed throughout the particles under starved, semi‐batch conditions. The tensile properties of films prepared from those latexes gave a clear indication that TMI was contributing to crosslinking . Although they used a different surfactant (sodium dihexyl sulfosuccinate, MA‐80), a lower BA/MMA ratio (≈60/40; wt./wt.)…”
Section: Resultsmentioning
confidence: 99%
“…Mohammed et al reported that higher concentrations of NCO groups at particles' surface had a negative effect on the shelf storage stability of TMI latexes . The proximity of those groups to water made them more susceptible to hydrolysis, resulting in the loss of colloidal stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinking contains one-component and two-component crosslinking. The common crosslinkers for two-component crosslinking mainly include carbodiimide [13,14], polyaziridine [15,16], and isocyanate [17][18][19]. One of the most important and pragmatic one-component crosslinking is the internal crosslinking, which implies the incorporation of polyfunctional monomers.…”
Section: Introductionmentioning
confidence: 99%
“…This is assumed to be due to a catalytic effect on NCO hydrolysis by COOH groups in MAA repeat units rather than to direct reaction between NCO and COOH groups because COOH groups are lower in the hierarchy of reactivity towards NCO groups compared to water. [27] When acetic acid (2 wt% based on total monomer in the formulation) was added to the B20-NA as-prepared latex (which did not contain MAA) immediately before casting the latex (this mixture being coded B20-NA-AA), the rate of NCO loss increased only by a factor of approximately two. Thus the rate of loss of NCO remained much lower than for the latexes in which MAA was incorporated.…”
Section: Studies Of Tmi Part I 1057mentioning
confidence: 99%